Multi-element heteroatom doped Co / Pt nano-catalyst derived based on cobalt-nitrogen pre-coordinated carbon precursor as well as preparation method and application of multi-element heteroatom doped Co / Pt nano-catalyst
By using a multivariate heteroatom doped Co/Pt nanocatalyst derived from cobalt-nitrogen precoordinated carbon precursor in the PEMFCs anode catalyst, the problems of high cost and insufficient activity stability of existing catalysts are solved, and catalytic effects with high activity, low cost and high stability are achieved.
Patent Information
- Application Number
- CN202510021788.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-07
AI Technical Summary
The anode catalysts of existing PEMFCs have problems with high cost and insufficient activity stability, especially the Pt/C catalysts are expensive and have low activity.
Multivariate heteroatom doped Co/Pt nanocatalysts derived from cobalt-nitrogen precoordinated carbon precursors are adopted, and the utilization rate of precious metal atoms is uniformly loaded by solvent-assisted metal-organic framework self-assembly technology, combined with physical suction filtration and high-temperature heat treatment methods, and platinum particles are uniformly loaded to improve the utilization rate of precious metal atoms.
It achieves the reduction of precious metals and the high activity and stability of the catalyst while ensuring excellent activity. It is suitable for PEMFCs anode catalyst, which significantly increases the current density of the hydroxide reaction.
Smart Images

Figure CN119812365A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a multi-heteroatom doped Co / Pt nanocatalyst derived from a cobalt-nitrogen pre-coordinated carbon precursor and a preparation method and application thereof, belonging to the technical field of fuel cell catalysts and preparation thereof. Background Art
[0002] Hydrogen energy (H 2 ) is considered to be an ideal energy carrier to replace fossil fuels. Proton exchange membrane fuel cells (PEMFCs) can directly convert the chemical energy in hydrogen into electrical energy through hydrogen oxidation reaction. They have the characteristics of high energy utilization, clean and pollution-free, so they have good commercial application prospects.
[0003] However, the anode HOR reaction of PEMFCs faces serious challenges. It is well known that Pt / C catalyst is currently one of the best choices for the anode HOR reaction of PEMFCs, but Pt / C catalyst is expensive. Therefore, the development of high-activity, high-stability, low-cost low-platinum HOR catalyst is a key issue that urgently needs to be solved. Summary of the invention
[0004] In order to solve the above technical problems existing in the anode catalysts of existing PEMFCs, the present invention provides a multi-heteroatom doped Co / Pt nanocatalyst derived from a cobalt-nitrogen pre-coordinated carbon precursor, and a preparation method and application thereof.
[0005] The technical solution of the present invention:
[0006] One of the purposes of the present invention is to provide a method for preparing a multi-heteroatom doped Co / Pt nanocatalyst, the method comprising the following steps:
[0007] (1) mixing a bromine source or a sulfur source, a cobalt salt, a zinc salt and a solvent, and stirring the mixture under ultrasonic conditions to obtain a precursor solution;
[0008] (2) adding the ligand solution to the precursor solution under stirring conditions, dispersing and then precipitating at room temperature to obtain a metal-organic framework precursor solution;
[0009] (3) centrifuging the metal-organic framework precursor solution, washing the precipitate, and drying it under vacuum conditions to obtain a purple cobalt-nitrogen coordinated carbon source powder;
[0010] (4) heat-treating the cobalt-nitrogen coordinated carbon source powder under a reducing atmosphere to obtain a coordination polymer catalyst powder in which nitrogen lone pair electrons anchor cobalt;
[0011] (5) mixing the nitrogen lone pair electron anchored cobalt coordination polymer catalyst powder, chloroplatinic acid solution and water, and stirring them evenly with a magnetic stirrer to obtain a Pt-loaded nitrogen lone pair electron anchored cobalt coordination polymer aqueous solution;
[0012] (6) The aqueous solution of the coordination polymer of nitrogen lone pair electron anchored cobalt loaded with Pt is filtered through a microporous filter membrane, washed with deionized water, and vacuum dried. The dried black powder is pyrolyzed in a reducing atmosphere to obtain a multi-heteroatom doped Co / Pt nanocatalyst.
[0013] Further specified, in (1), the bromine source is sodium bromide, potassium bromide, hexadecyltrimethylammonium bromide or benzalkonium bromide; the sulfur source is nickel disulfide, cobalt disulfide, sodium dodecyl sulfate or sodium dodecylbenzene sulfonate; the cobalt salt is cobalt acetylacetonate, cobalt dichloride, cobalt nitrate or cobalt carbonate; the zinc salt is zinc acetate, zinc chloride, zinc nitrate or zinc sulfide; and the solvent is methanol.
[0014] It is further defined that in (1), the amount ratio of the bromine source or sulfur source, the cobalt salt and the zinc salt is (0.01-0.4) g: (1-10) mmol: 1 mmol, and the amount of the solvent is 110-130 mL.
[0015] It is further defined that the usage ratio of the bromine source, sulfur source, cobalt salt and zinc salt in (1) is (0.05-0.3) g: (0.05-0.3) g: (2-8) mmol: 1 mmol.
[0016] It is further defined that the usage ratio of the bromine source, sulfur source, cobalt salt and zinc salt in (1) is (0.1-0.2) g: (0.1-0.2) g: (3-5) mmol: 1 mmol.
[0017] It is further defined that the ultrasonic stirring time in (1) is 0.5 to 1.5 h.
[0018] It is further defined that the ligand concentration in the metal-organic framework precursor solution obtained in (2) is 1.02 mol / L.
[0019] It is further defined that the dispersion time at room temperature in (2) is 18 to 20 hours; and the sedimentation time is 6 to 8 hours.
[0020] It is further defined that the dispersion treatment in (2) includes ultrasound and stirring, the ultrasound power is 60-100 W, the time is 15-30 min; the stirring speed is 300-400 rpm, and the time is 18-20 h.
[0021] It is further defined that the centrifugal speed in (3) is 6000-11000 rpm, and the time is 30-60 min.
[0022] It is further defined that the centrifugal speed in (3) is 7000 to 10000 rpm.
[0023] It is further defined that the centrifugal speed in (3) is 8000-9000 rpm.
[0024] It is further defined that the drying temperature in (3) is 30 to 100° C. and the drying time is 12 to 24 hours.
[0025] It is further defined that the drying temperature in (3) is 40-90°C h.
[0026] It is further defined that the drying temperature in (3) is 60-80°C h.
[0027] It is further defined that the heat treatment temperature in (4) is 600-1000°C and the time is 8-12h.
[0028] It is further defined that the heating rate of the heat treatment process in (4) is 2 to 5°C / min.
[0029] It is further defined that the heat treatment temperature in (4) is 750-950°C.
[0030] It is further defined that the heat treatment temperature in (4) is 800-900°C.
[0031] Further, the reducing atmosphere in (4) is H 2 and Ar mixed atmosphere.
[0032] It is further defined that the concentration of the chloroplatinic acid solution in (5) is 0.0244 mol / L, and the mass volume ratio of the coordination polymer catalyst powder with nitrogen lone pair electrons anchored to cobalt, the chloroplatinic acid solution and water is 1 g: (1-100) mL: (100-1000) mL.
[0033] It is further defined that the mass volume ratio of the coordination polymer catalyst powder in which the nitrogen lone pair electrons anchor the cobalt in (5), the chloroplatinic acid solution and water is 1 g: (5-50) mL: (500-1000) mL.
[0034] It is further defined that the mass volume ratio of the coordination polymer catalyst powder in which the nitrogen lone pair electrons anchor the cobalt in (5), the chloroplatinic acid solution and water is 1 g: (8-30) mL: (800-1000) mL.
[0035] It is further defined that the magnetic stirring speed in (5) is 300-400 rpm and the time is 2-4 h.
[0036] It is further defined that the pore size of the microporous filter membrane in (6) is 20 μm and the diameter is 50 mm.
[0037] It is further defined that the drying temperature in (6) is 30 to 100° C. and the drying time is 6 to 12 hours.
[0038] It is further defined that the drying temperature in (6) is 40 to 90°C.
[0039] It is further defined that the drying temperature in (6) is 60-80°C.
[0040] It is further defined that the pyrolysis temperature in (6) is 100-700°C and the time is 6-8h.
[0041] It is further defined that the pyrolysis temperature in (6) is 300-600°C.
[0042] It is further defined that the pyrolysis temperature in (6) is 400-500°C.
[0043] It is further defined that the heating rate during the pyrolysis process in (6) is 2 to 5°C / min.
[0044] Further, the reducing atmosphere in (6) is H 2 and Ar mixed atmosphere.
[0045] The second object of the present invention is to provide a multi-heteroatom doped Co / Pt nanocatalyst prepared by the above method.
[0046] The third object of the present invention is to provide an application of the above-mentioned multi-heteroatom doped Co / Pt nanocatalyst, specifically used as an anode catalyst for PEMFCs.
[0047] Further defined, the beneficial effects of using HOR as anode electrocatalyst material to catalyze the hydrogen oxidation reaction at the anode in PEMFCs are:
[0048] The present invention adopts solvent-assisted metal-organic framework (SOMF) self-assembly technology based on cobalt-nitrogen pre-coordinated carbon precursor, uses methanol as solvent medium, and improves the dispersibility and morphological characteristics of the material by doping S or Br to obtain a metal-organic framework (MOF) precursor, and further adopts a method of combining physical filtration and high-temperature heat treatment to make platinum (Pt) particles uniformly loaded in MOF-derived materials, thereby obtaining a multi-heteroatom doped Co / Pt nanocatalyst derived from cobalt-nitrogen pre-coordinated carbon precursor. The catalyst improves the utilization rate of noble metal atoms while ensuring excellent activity, thereby achieving the purpose of reducing the amount of noble metals used. Experimental results show that the three samples (Pt@Co-BrNC, Pt@Co-SNC and Pt@Co-NC) have good performance in 0.1MHClO 4 The current density in the 2 , 2.133mA / cm 2 and 1.782mA / cm 2 , is a potential PEMFC anode catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1This is a scanning electron micrograph of the Pt@Co-BrNC prepared in Example 1;
[0050] Figure 2 This is a scanning electron micrograph of the Pt@Co-SNC prepared in Example 2;
[0051] Figure 3 This is a scanning electron micrograph of the Pt@Co-NC prepared in Comparative Example 1;
[0052] Figure 4 X-ray diffraction peaks of Co-BrNC, Co-SNC and Co-NC prepared in Examples 1 to 2 and Comparative Example 1;
[0053] Figure 5 X-ray diffraction peaks of Pt@Co-BrNC, Pt@Co-SNC and Pt@Co-NC prepared in Examples 1 to 2 and Comparative Example 1;
[0054] Figure 6 The linear sweep voltammogram of the Pt@Co-BrNC catalyst prepared in Example 1 measured under acidic conditions and at different rotation speeds;
[0055] Figure 7 The linear sweep voltammogram of the Pt@Co-SNC catalyst prepared in Example 1 measured under acidic conditions and at different rotation speeds;
[0056] Figure 8 This is the linear sweep voltammogram of the Pt@Co-NC catalyst prepared in Comparative Example 1 measured under acidic conditions and at different rotation speeds. DETAILED DESCRIPTION
[0057] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0058] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0059] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0060] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0061] Example 1
[0062] (1) Dissolve 3 mmol of cobalt nitrate and 1 mmol of zinc nitrate in 30 mL of methanol and stir to obtain a metal solution for later use;
[0063] 0.15 g of hexadecyltrimethylammonium bromide was dissolved in 10 mL of methanol, stirred evenly, mixed with the metal solution, and ultrasonically treated at room temperature for 20 min to obtain a uniform precursor solution.
[0064] (2) Dissolve 1.96 g of dimethylimidazole in 20 mL of methanol solution and stir evenly to obtain a ligand solution for later use;
[0065] At a speed of 300-400 rpm, the precursor solution is slowly added to the ligand solution to obtain a dark purple solution, which is first ultrasonically dispersed at room temperature, with a specific ultrasonic power of 80 W and a time of 30 minutes; then stirred and dispersed, with a specific stirring speed of 320 rpm and a time of 19 hours, and finally precipitated for 7 hours. The purpose of mixing the metal solution and the ligand solution to obtain a uniform dispersed solution is to form a uniform reaction environment, so that sufficient coordination reaction occurs between the metal ions and the organic ligands, thereby reducing crystal defects.
[0066] (3) After precipitation, the mixture was centrifuged at 8000 rpm / min, washed with anhydrous ethanol 5 times, and dried at 70°C under vacuum for 12 h to obtain a purple powder.
[0067] (4) The purple powder obtained in step (3) is heat-treated under a reducing atmosphere. Specifically, the temperature is raised to 900° C. at a heating rate of 5° C. / min, kept at this temperature for 2 h, and naturally cooled to room temperature to obtain a coordination polymer catalyst powder with nitrogen lone pair electrons anchoring cobalt, named Co-BrNC.
[0068] (5) 50 mg of Co-BrNC was added to 50 mL of deionized water and stirred evenly. Then, 0.5 mL of 0.20244 mol / L chloroplatinic acid solution was added and magnetic stirring was performed at room temperature for 2 h to obtain a uniformly dispersed Pt-loaded Co-BrNC aqueous solution.
[0069] (6) The Pt-loaded Co-BrNC aqueous solution obtained in step (5) was filtered using a microporous filter membrane with a pore size of 20 μm and a diameter of 50 mm, washed with deionized water, and dried in a vacuum oven at 70° C. for 12 h to obtain a black powder.
[0070] (7) The black powder obtained in step (6) was heated to 400 °C. 2 The catalyst was pyrolyzed in a mixed atmosphere of Ar / Co at a specific temperature of 500°C for 6 to 8 hours and then naturally cooled to room temperature to obtain a multi-heteroatom doped Co / Pt nanocatalyst derived from a cobalt-nitrogen pre-coordinated carbon precursor, named Pt@Co-BrNC.
[0071] Example 2
[0072] The difference between this embodiment and embodiment 1 is that 0.15 g of sodium dodecyl sulfate is used to replace 0.15 g of hexadecyltrimethylammonium bromide in step (1), and the remaining process steps and parameter settings are the same as those in embodiment 1.
[0073] The coordination polymer catalyst powder with nitrogen lone pair electrons anchoring cobalt obtained in step (4) of this embodiment is named Co-SNC, and the multi-heteroatom doped Co / Pt nanocatalyst derived from a cobalt-nitrogen pre-coordinated carbon precursor obtained in step (7) is named Pt@Co-SNC.
[0074] Comparative Example 1
[0075] The difference between this comparative example and Example 1 is that the amount of hexadecyltrimethylammonium bromide used in step (1) is 0 g, and the remaining process steps and parameter settings are the same as those in Example 1.
[0076] The coordination polymer catalyst powder with nitrogen lone pair electrons anchoring cobalt obtained in step (4) of this example is named Co-NC, and the multi-heteroatom-doped Co / Pt nanocatalyst derived from a cobalt-nitrogen pre-coordinated carbon precursor obtained in step (7) is named Pt@Co-NC.
[0077] Effect example
[0078] (1) The microstructures of Pt@Co-BrNC, Pt@Co-SNC and Pt@Co-NC prepared in Examples 1 to 2 and Comparative Example 1 were characterized. Figures 1 to 3As shown in the figure, it can be observed that Pt@Co-BrNC exhibits excellent dispersibility and high specific surface area characteristics due to its regular cubic structure, clear metal framework, uniform particle size and reasonable gap distribution. These characteristics provide Pt@Co-BrNC with a large number of accessible active sites, thereby enhancing its performance. In contrast, although Pt@Co-SNC also has good dispersibility, it is slightly insufficient in terms of shape regularity and particle uniformity, which leads to a relatively small number of active sites. As for Pt@Co-NC, there is an obvious particle aggregation phenomenon, poor dispersion, irregular shape, and therefore relatively limited exposed active sites.
[0079] (2) The X-ray diffraction peak comparison spectra of Co-BrNC, Co-SNC and Co-NC prepared in Examples 1 to 2 and Comparative Example 1 are as follows Figure 4 As shown in the figure, the diffraction peak positions of Co-BrNC and Co-SNC are slightly shifted compared with Co-NC, which indicates that Br and S are incorporated into the lattice as substitutional atoms. The slight strain caused by the incorporation of Br and S also leads to different degrees of diffraction peak shift of Co-BrNC and Co-SNC.
[0080] (3) The X-ray diffraction peak comparison spectra of Pt@Co-BrNC, Pt@Co-SNC and Pt@Co-NC prepared in Examples 1 to 2 and Comparative Example 1 are as follows Figure 5 As shown in the figure, it can be seen that the diffraction peak positions of Pt@Co-BrNC and Pt@Co-SNC are shifted to smaller angles compared with Pt@Co-NC, which indicates that the introduction of Pt helps to release the original stress and lattice structure, thereby further changing its lattice distortion state.
[0081] (4) Electrodes were prepared with Pt@Co-BrNC, Pt@Co-SNC and Pt@Co-NC as catalysts, and linear sweep voltammetry (LSV) tests were performed. The specific operation was as follows: 5 mg of Pt@Co-BrNC, 5 mg of Pt@Co-SNC and 5 mg of Pt@Co-NC were weighed, mixed with 2 mg of carbon black and dissolved in 1.5 mL of anhydrous ethanol, ultrasonically dispersed evenly, and then 0.5 mL of 0.5% Nafion solution was added, and ultrasonically dispersed for 2 hours to obtain a uniform catalyst slurry. The catalyst slurry was then evenly coated on the glassy carbon electrode and heated under H 2 Linear sweep voltammetry (LSV) tests were performed under atmosphere.
[0082] In 0.1 M HClO 4 The linear sweep voltammograms of the three catalysts Pt@Co-BrNC, Pt@Co-SNC and Pt@Co-NC measured at different rotation speeds are shown in Figure 2. Figures 6 to 8As shown in the figure, it can be seen that in 0.1M HClO 4 The current density of the three catalysts Pt@Co-BrNC, Pt@Co-SNC and Pt@Co-NC at 1600rpm was 2.354mA / cm 2 , 2.133mA / cm 2 and 1.782mA / cm 2 , indicating that the catalyst prepared in the above example has excellent catalytic activity in hydrogen oxidation reaction.
[0083] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing a multi-heteroatom doped Co / Pt nanocatalyst, characterized in that: include: (1) mixing a bromine source or a sulfur source, a cobalt salt, a zinc salt and a solvent, and stirring the mixture under ultrasonic conditions to obtain a precursor solution; (2) adding the ligand solution to the precursor solution under stirring conditions, dispersing and then precipitating at room temperature to obtain a metal-organic framework precursor solution; (3) centrifuging the metal-organic framework precursor solution, washing the precipitate, and drying it under vacuum conditions to obtain a purple cobalt-nitrogen coordinated carbon source powder; (4) heat-treating the cobalt-nitrogen coordinated carbon source powder under a reducing atmosphere to obtain a coordination polymer catalyst powder in which nitrogen lone pair electrons anchor cobalt; (5) mixing the nitrogen lone pair electron anchored cobalt coordination polymer catalyst powder, chloroplatinic acid solution and water, and stirring them evenly with a magnetic stirrer to obtain a Pt-loaded nitrogen lone pair electron anchored cobalt coordination polymer aqueous solution; (6) The aqueous solution of the coordination polymer of nitrogen lone pair electron anchored cobalt loaded with Pt is filtered through a microporous filter membrane, washed with deionized water, and vacuum dried. The dried black powder is pyrolyzed in a reducing atmosphere to obtain a multi-heteroatom doped Co / Pt nanocatalyst.
2. The preparation method according to claim 1, characterized in that: (1) The bromine source is sodium bromide, potassium bromide, hexadecyltrimethylammonium bromide or benzalkonium bromide; the sulfur source is nickel disulfide, cobalt disulfide, sodium dodecyl sulfate or sodium dodecylbenzene sulfonate; the cobalt salt is cobalt acetylacetonate, cobalt dichloride, cobalt nitrate or cobalt carbonate; the zinc salt is zinc acetate, zinc chloride, zinc nitrate or zinc sulfide; the ligand is benzimidazole, 2-methylimidazole, 3,5-lutidine or 1,2,4-triazole; and the solvent is methanol.
3. The preparation method according to claim 1, characterized in that: (1) The dosage ratio of the bromine source or sulfur source, the cobalt salt and the zinc salt is (0.01-0.4) g: (1-10) mmol: 1 mmol.
4. The preparation method according to claim 1, characterized in that: (2) The ligand concentration in the obtained metal-organic framework precursor solution is 1.02 mol / L.
5. The preparation method according to claim 1, characterized in that: (2) The dispersion time at room temperature is 18 to 20 hours; the aging time is 6 to 8 hours.
6. The preparation method according to claim 1, characterized in that: (4) The heat treatment temperature is 600-1000°C and the time is 8-12h.
7. The preparation method according to claim 1, characterized in that: (5) The concentration of the chloroplatinic acid solution is 0.0244 mol / L, and the mass volume ratio of the coordination polymer catalyst powder with nitrogen lone pair electrons anchored to cobalt, the chloroplatinic acid solution and water is 1 g: (1-100) mL: (100-1000) mL.
8. The preparation method according to claim 1, characterized in that: (6) The pyrolysis temperature is 100-700°C and the time is 6-8h.
9. A multi-heteroatom doped Co / Pt nanocatalyst prepared by the method according to any one of claims 1 to 8.
10. An application of the multi-heteroatom doped Co / Pt nanocatalyst according to claim 9, characterized in that: Used as anode catalyst in PEMFCs.
Citation Information
Patent Citations
Application of heteroatom-doped porous-carbon-coated Co9S8 composite catalyst
CN109713326A
Nitrogen-phosphorus co-doped metal organic framework encapsulated platinum-cobalt-based alloy as well as preparation method and application thereof
CN112467150A
Preparation method and application of platinum-cobalt alloy catalyst
CN116504997A
Method for preparing cobalt-isolated platinum nanoparticle catalyst by two-step annealing method and application of cobalt-isolated platinum nanoparticle catalyst
CN116581316A
Fabrication method and application of cobalt and nitrogen co-doped three-dimensional structured carbon matrix
US20240228296A1